Study of the radiomodifier effect of Pityrocarpa moniliformis extract - João Victor Torres de Moraes; Ricardo Luiz Calazans Luna Filho; Williams Nascimento de Siqueira; Hianna Arely Milca Fagundes Silva; Dewson Rocha Pereira; Ana Maria Mendonça de Albuquerque Melo (Brazilian Journal of Radiation Sciences, 2019)
Ionizing radiation has been applied in several areas of knowledge, among them the study of the radiomodifier activity of natural substances. These substances can modify the cellular response to the damage induced by the radiation. Therefore, this work aimed to evaluate the radiomodifier action of Pityrocarpa moniliformis extract on Biomphalaria glabrata embryos exposed to 60Co gamma radiation. Initially, toxicity tests were performed on the extract against the B. glabrata embryos for the choice of concentration that did not cause death and embryonic malformation. Then, the antioxidant activity of the P. moniliformis extract with flavonoids and phenolic compounds was evaluated by means of the ABTS method. To evaluate the radiomodifier activity of the extract, embryos were selected in the blastula stage and irradiated with 7.5 Gy in a 60Co source (gammacell-Co60). Then, the embryos were exposed for 24 h to the extract of P. moniliformis at a concentration of 250 μg/mL. The results showed that the extract of P. moniliformis presents flavonoids and enzymatic inhibition by ABTS, which demonstrates the presence of antioxidant compounds. However, the tests of the radiomodifier activity did not present radioprotective effect for embryos exposed to ionizing radiation.